PSIKOEDUKASI SMART PARENTING: MENCIPTAKAN GENERASI SEHAT DAN BEBAS STUNTING (UPAYA MENCEGAH STUNTING MELALUI PERSPEKTIF PENGASUHAN YANG EFEKTIF) - Abdiah Bahar, Ririn Nur; Fatonah, Siti; Shavina Santri, Vania; Santimah, Santimah; Rosdiana, Rosdiana (Gapenas Publisher, 2024)
Stunting is one of the problems that occur in Indonesia. Stunting not only affects the delay in physical development of children, but also has psychological impacts. Various efforts have been made by the government to prevent the increasing number of stunting. However, it cannot be denied that in fact in several areas there are still obstacles related to this, especially in Terumbu Village, Kasemen District, Serang City, Banten. Thus, the purpose of this community service activity is to prevent the incidence of toddlers in Terumbu Village. The approach method used is to provide psychoeducation related to effective parenting patterns so that children can grow and develop according to their age. Participants in this activity were 55 parents who were local residents. The results of this activity can show an increase in residents' understanding by 80% regarding parenting patterns and stunting. It is hoped that this psychoeducation can be carried out continuously to reduce stunting rates.